Network anomaly detection based on TCM-KNN and genetic algorithm - LI Yang1; FANG Bin-xing1; GUO Li1; TIAN Zhi-hong1; ZHANG Yong-zheng1; JIANG Wei1 (Tongxin xuebao)
A network anomaly detection scheme based on TCM-KNN algorithm was proposed.Moreover,genetic algo-rithm（GA） based instance selection was introduced to boost the detection performance,meanwhile reduce the computa-tional cost for TCM-KNN.A series of experimental results demonstrate the proposed method is effective,the instance se-lection mechanism also improves TCM-KNN and makes it be a good candidate for anomaly detection in practice.